Performance analysis of AL amyloidosis cardiac biomarker staging systems with special focus on renal failure and atrial arrhythmia - Dittrich, Tobias; Benner, Axel; Kimmich, Christoph; Siepen, Fabian aus dem; Veelken, Kaya; Kristen, Arnt; Bochtler, Tilmann; Katus, Hugo; Müller-Tidow, Carsten; Hegenbart, Ute; Schönland, Stefan (Haematologica, 2019)
Systemic light chain amyloidosis is a rare and life-threatening disorder, for which accurate risk stratification is crucial. Current cardiac staging systems (MAYO2004, MAYO3b, and MAYO2012) are mainly based on biomarkers, which have uncertain reliability in the context of atrial fibrillation, arrhythmia or pacemaker stimulation as well as renal insufficiency. We compared the performance of the established staging systems with particular regard to these comorbidities in 1,224 patients with systemic light chain amyloidosis diagnosed at our center from July 2002 until March 2017. We first characterized the subsets with an estimated glomerular filtration rate <50 mL/min/1.73 m2 (415 patients) and any kind of atrial arrhythmia (183 patients) as unique high-risk subgroups with similarly increased cardiac biomarkers (χ2-test, all P<0.001). This resulted in a shift towards higher risk stages and reduced median overall survival compared to those of patients with better kidney function or without atrial arrhythmia in univariate analyses (13 vs. 46 months and 17 vs. 53 months, respectively; both P<0.001). Performance analysis revealed that predictions in the entire cohort were least precise with the MAYO2004 staging system and most precise with the MAYO3b system. This performance pattern was almost preserved for patients with an estimated glomerular filtration rate <50 mL/min/1.73 m2, but less so for those with atrial arrhythmias. The MAYO3b staging system was most robust. Importantly, atrial arrhythmia retained its prognostic value in multivariable analysis including age, difference between involved and uninvolved free light chains, and any staging system, while estimated glomerular filtration rate <50 mL/min/1.73 m2 was not statistically significant in multivariable analysis with the MAYO3b staging system. In conclusion, our results favor the MAYO3b staging system due to its consistently best performance and retained applicability in the subgroups with atrial arrhythmia and estimated glomerular filtration rate <50 mL/min/1.73 m2.
Gesehen am 04.09.2019